THE STRUCTURE STRENGTH ANALYSIS ON THE FURROW PLOUGH IN THE AGRICULTURAL MACHINERY - ZHANG ChunLing (Jixie qiangdu, 2016)
The furrow plough’s strength was designed by theoretical analyses and experimental strain analyses to make sure the design reasonable and accurate. As fully-loaded tractors run at a low speed,by theoretically analyzing the stretch-bending combined-deformation strength,the calculated results were used as design basis. By experimental analyses and the strain rosette theory,under the same conditions,strain values are measured by resistance strain gauges as the calculation basis. The experimental analyses further verify the security of theoretical calculations. When designing agricultural machinery,combining the theory and experiments ensures the components’ reliability. So strain analyses are good and simple methods to design the complex structures.